2020
DOI: 10.1007/s40121-020-00369-4
|View full text |Cite
|
Sign up to set email alerts
|

Co-Existence of Carbapenemase-Encoding Genes in Acinetobacter baumannii from Cancer Patients

Abstract: Introduction Acinetobacter baumannii is an opportunistic pathogen, which can acquire new resistance genes. Infections by carbapenem-resistant A. baumannii (CRAB) in cancer patients cause high mortality. Methods CRAB isolates from cancer patients were screened for carbapenemase-encoding genes that belong to Ambler classes (A), (B), and (D), followed by genotypic characterization by enterobacterial-repetitive-Intergenic-consensus–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 58 publications
2
10
1
Order By: Relevance
“…So, CDT represents a good screening test being simple, not time or money consuming with accepted sensitivity and specificity. Some isolates showed phenotypic MBL activity with negative PCR results that could be simply explained by presence of other MBLs genes that we did not look for in our study eg blaSPM, blaSIM, blaGIM which were reported by a recent study in Egypt [21]. On the other hand, some isolates showed no phenotypic MBL activity although PCR results were positive that could be due to the environmental factors interfering with the phenotypic expression of the MBL genes and compromising the sensitivity of the phenotypic method compared to the molecular method [22].…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…So, CDT represents a good screening test being simple, not time or money consuming with accepted sensitivity and specificity. Some isolates showed phenotypic MBL activity with negative PCR results that could be simply explained by presence of other MBLs genes that we did not look for in our study eg blaSPM, blaSIM, blaGIM which were reported by a recent study in Egypt [21]. On the other hand, some isolates showed no phenotypic MBL activity although PCR results were positive that could be due to the environmental factors interfering with the phenotypic expression of the MBL genes and compromising the sensitivity of the phenotypic method compared to the molecular method [22].…”
Section: Discussioncontrasting
confidence: 48%
“…So, our study was focused on these three genes. However other MBL genes have been reported in Egypt less commonly [21]. It is worth mention that although reports of MBL genes (IPM, VIM and NDM) among GNB have been published worldwide yet reports from Africa and Middle East countries [25][26][27][28][29][30][31] are relatively limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We could not find A. baumannii isolates harboring bla VIM , bla GES , bla VEB , and bla NDM genes. In contrast, a high prevalence rate of bla NDM gene has been observed in CRAB isolates from Egyptian patients [ 22 ]. The bla OXA-23-like was more prevalent in our study, which is in agreement with previous studies [ 17 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…32,62,63 We have summarized several studies in which ESKAPE pathogens were isolated from patients with cancer since 2015 in Table 2. 31,[59][60][61][62][64][65][66][67][68][69][70][71][72][73][74] These illustrate the prevalence of MDR in different ESKAPE pathogens and highlight that prior antibiotic exposure and hospital-acquired infections are the major risk factors for developing antibiotic resistance in patients with cancer. For Figure 1, we derived data from the National Healthcare Safety Network (NHSN) 2015 to 2017 adult and pediatric antibiotic resistance reports 75,76 to illustrate differences between the percentage of central line-associated bloodstream infections by ESKAPE pathogens that tested nonsusceptible to selected antimicrobial agents.…”
Section: The Use Of Antibiotics and The Burden Of Antibiotic Resistance In Patients With Cancermentioning
confidence: 95%